Consideration of eyeball length and prismatic side-effects of spectacle lenses in strabismus surgery: a randomised, double-blind interventional study - Beisse, Flemming; Koch, Matthias; Uhlmann, Lorenz; Beisse, Christina (Graefe's archive for clinical and experimental ophthalmology, 2020)
Potential sources of error in dosage planning in strabismus surgery are (a) prismatic side-effects of spectacle lenses when measuring the preoperative angle with the alternating prism cover test and (b) a potential influence of eye ball axial length on dose response. As both errors take effect in opposite directions, many strabismus surgeons set aside their consideration. This study investigates whether considering both factors for dosage planning yields better operative results.
Gesehen am 09.09.2021